The Indirect Threats of Desert Locust Infestation on Honeybees in Ethiopia - Zemene Worku; Addisu Bihonegn; Desalegn Begna; Sebsib Ababor; Arse Gebeyehu (Advances in Agriculture)
This review focuses on the potential effects of a desert locust infestation on Ethiopian honeybees. Data on the country’s infestation, locust activity, honeybee foraging behavior, pesticide kinds, and application rates were collected and analyzed in connection to honeybee life and performance. Desert locust has damaged a considerable number of plants of various kinds, possibly causing pollen and nectar loss. As a result, honeybees are likely to produce less brood, less honey, suffer from poor health, and abscond. Besides, studies suggested that the use of pesticides to control the locust could directly harm honeybees. The pesticide was used for 21 days in a row to cover a huge region infected with locusts, which could have had a severe effect on honeybees. The probability of an influence is also indicated by the overlap of pesticide administration with honeybee foraging seasons and hours. Furthermore, forager bees leave their hive 1 to 13 times per day, spending about 3 hours outside each time, indicating higher chemical exposure. Malathion is one of the pesticides that could harm honeybees, while there is no comprehensive list of the chemicals used on the internet or anywhere else. Finally, the current desert locust invasion and eradication operation in Ethiopia may have caused substantial damage to honeybees as a result of bee forage loss and pesticide hazard, emphasizing the need for future precautions. Because this is speculative work based on evidence, detailed survey research is recommended to determine the actual impact imposed on honeybees.